The Influence of Financial Department Employee Satisfaction on Budget Efficiency Performance with Work Motivation as an Intervening Variable at Gunung Jati Hospital, Cirebon City - Purwanto, Agtika; Herlina, Ellin; Kardiyati, Endah Nurhawaeny (CV. Strata Persada Academia, 2025)
Budget efficiency is crucial for the financial sustainability and service quality of public healthcare institutions. This study examines the influence of employee satisfaction on budget efficiency performance in the Financial Department of Gunung Jati Regional Hospital, Cirebon City, with work motivation as an intervening variable. Utilizing an explanatory research design, data were collected from 42 financial department employees through questionnaires, employing a 5-point Likert scale. The study also incorporated secondary financial data to strengthen the analysis. Multiple regression and path analysis, conducted using SPSS and AMOS software, revealed a significant positive relationship between employee satisfaction and budget efficiency performance, with work motivation playing a mediating role. Findings indicate that higher employee satisfaction enhances work motivation, which in turn improves budget efficiency. These results highlight the importance of implementing policies that enhance job satisfaction and motivation, such as optimizing benefits, career development programs, and performance-based incentives. The study contributes to the existing literature on financial and human resource management in public healthcare settings and provides practical recommendations for improving budget performance at regional hospitals in Indonesia.